Rehabilitation of cognitive deficits poststroke: protocol for a systematic review and meta-analysis of randomised controlled trials of non-pharmacological interventions - Rose Galvin; Mairead O Donoghue; Pauline Boland; Susan Coote; Sara Hayes (BMJ Open)
Introduction Stroke is among the leading causes of death and disability worldwide. Poststroke cognitive impairment is a common sequela of stroke. The burden of cognitive impairment poststroke has significant impacts on the individual poststroke, their family and wider society. Despite the prevalence and associated burden of poststroke cognitive impairment, the optimal approach to rehabilitate cognitive deficits poststroke has yet to be established. A range of conservative interventions for cognitive impairment poststroke exist including self-efficacy training, physical activity interventions, neuropsychological interventions, electronic interventions, music therapy and occupational therapies. This systematic review aims to explore the totality of evidence with regard to non-pharmacological rehabilitation interventions wherein the primary or secondary aim is to improve cognitive function in individuals poststroke.Methods and analysis A systematic review of randomised controlled trials which investigate the effectiveness of interventions wherein the primary or secondary aim is to improve cognitive function in individuals poststroke will be conducted (August 2019). The following electronic databases will be searched: PubMed, Embase, CINAHL, CENTRAL and PsycInfo. Reference lists of all identified studies will be reviewed to identify additional studies for inclusion. Titles and abstracts will be screened independently by two review authors for inclusion and exclusion. Any disagreement regarding inclusion will be resolved by discussion or by referral to a third assessor if necessary. Methodological quality will be assessed using the Cochrane Risk of Bias Tool for Randomised Controlled Trials. Meta-analyses will be performed if studies are sufficiently homogeneous. The review will be reported in accordance to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement.Ethics and dissemination As this systematic review will collect secondary data only, ethical approval is not required. Findings will be disseminated through presentations and peer-reviewed journals.Trial registration number CRD42019125289.